AIDS Vaccination Studies Using an Ex Vivo Feline Immunodeficiency Virus Model: Detailed Analysis of the Humoral Immune Response to a Protective Vaccine - Mazzetti, Paola (American Society for Microbiology, 1999)
The feline immunodeficiency virus (FIV) cat model is extensively used to investigate possible vaccination approaches against AIDS in humans. Although consistent levels of protection have been achieved with FIV, as with other model systems, by immunizing with whole inactivated virus or fixed infected cells, the mechanisms responsible for protection are elusive. In previous studies we showed that cats immunized with a vaccine consisting of fixed infected cells were protected or unprotected against cell-free or cell-associated FIV challenge depending on the time interval between completion of vaccination and challenge. In an attempt to define possible humoral immune correlates of protection, selected sera harvested at the times of challenge from such cats were examined for anti-FIV-antibody titers and properties by using binding and functional immunological assays. Binding assays included quantitative Western blotting, enzyme-linked tests for antibodies to FIV glycoproteins and immunodominant linear epitopes, and tests for measuring conformation dependence and avidity of anti-viral-envelope antibodies. Functional assays included virus neutralization performed with two different cell substrates, complement- and antibody-dependent virolysis, blocking of reverse transcriptase, and an assay that measured the ability of sera to prevent FIV growth in cocultures of infected and uninfected cells. Despite the wide spectrum of parameters investigated, no correlation between vaccine-induced protection and the humoral parameters measured was noted.